Answer:
![x= -(12)/(25)](https://img.qammunity.org/2020/formulas/chemistry/middle-school/u20fbtcpszq391yilmg7gp80115v47uzjh.png)
![y= (26)/(25)](https://img.qammunity.org/2020/formulas/chemistry/middle-school/5zoye248uh1ecanc9nh23zhvobj4oymsdb.png)
Step-by-step explanation:
5-10x + 5y = 15
1 9x + 3y = -6
To solve these two equations simultaneously:
; divide by 5
![y - 2x =2](https://img.qammunity.org/2020/formulas/chemistry/middle-school/ap7h9or9etfss3i0irexumvhng3ityowj2.png)
; Taking 2x to the other side.
Substituting for y in the other equation
![19x + 3y = -6](https://img.qammunity.org/2020/formulas/chemistry/middle-school/ib82foo0g9fvqbtsnrd30ge388o2bn88dp.png)
![19x + 3 * (2 + 2x)= -6](https://img.qammunity.org/2020/formulas/chemistry/middle-school/f1mbgwtusck30cc4mray9sriqnizlpcf9h.png)
![19x + 6 + 6x = -6](https://img.qammunity.org/2020/formulas/chemistry/middle-school/bjhe95b0ktkairaz0l2nb4ydoru1gm00c3.png)
; Making necessary commutations.
![x= -(12)/(25)](https://img.qammunity.org/2020/formulas/chemistry/middle-school/u20fbtcpszq391yilmg7gp80115v47uzjh.png)
Substituting this in
to find y
![y =2 + 2 * (-(12)/(25))](https://img.qammunity.org/2020/formulas/chemistry/middle-school/khc4asipjd7t0i9mxolhc0fkvg0d2pc54b.png)
![y= (26)/(25)](https://img.qammunity.org/2020/formulas/chemistry/middle-school/5zoye248uh1ecanc9nh23zhvobj4oymsdb.png)